Assessment of Sensory Processing and Executive Functions at the School: Development, Reliability, and Validity of EPYFEI-Escolar - Romero-Ayuso, Dulce; Toledano-González, Abel; Segura-Fragoso, Antonio; Triviño-Juárez, José Matías; Rodríguez-Martínez, Mª Carmen (Frontiers in Pediatrics, 2020)
The aim of this study was to determine the psychometric properties of the Assessment of Sensory Processing and Executive Functions at the School (EPYFEI-Escolar), a questionnaire designed to assess the sensory processing and executive functions as underlying processes for school participation. The total sample consisted of 536 children aged between 3 and 11 years old who lived in Spain. A total of 103 teachers completed the questionnaire. An exploratory factor analysis was conducted, which showed five main factors: 1) initiation, organization, execution and supervision of the action; 2) inhibitory control; 3) sensory processing; 4) emotional self-regulation and play, and 5) self-competence. Some of these factors were similar to those found in the EPYFEI for parents in the home context. The reliability of the analysis was high, both for the whole questionnaire and for the factors it is composed of. The results provide evidence of the potential usefulness of the EPYFEI-Escolar in school contexts for determining academic needs and difficulties of children; moreover, this tool can also be used to plan intervention programs in the school environment according to the needs of each child and school.